Przedmiot zobowiązania z umowy o twórczość naukową - Szyjewska-Bagińska, Joanna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The characteristic feature of creative work is its actual character. Its culmination is the creation of a copyrighted work - a legally protected good which, by the law itself, at the time of its establishment, becomes the subject of law. The legal relationship created by the contract for the performance of creative work is quite complex. In the concept of creativity one can distinguish two basic meanings: functional and material. Where the subject matter of the contract is the performance of scientific (as well as didactic) works, account should also be taken of the special rules governing the acquisition of rights to scientific works by a scientific institution and the special characteristics of scientific and didactic work. The structure of the contractual performance resulting from the conclusion of an agreement on scientific and didactic works indicates that the subject matter of such a contract is, to a greater extent, works in the functional sense rather than material. Analysis of the special regulation of Article 14 of the copyright law and the specific nature of the performance of the contract of scientific works, including didactics, leads to the conclusion that, unlike non-scientific works, the subject matter of a scientific works contract is the creator’s obligation related to the performance of a designated work or to the provision of services, rather than having the copyright to the work.